Nitrogen Mineralization of a Loam Soil Supplemented with Organic–Inorganic Amendments under Laboratory Incubation - Abbasi, M. Kaleem; Khaliq, Abdul (Frontiers in Plant Science, 2016)
The quantification of nitrogen (N) supplying capacity of organic amendments applied to a soil is of immense importance to examine synchronization, N release capacity, and fertilizer values of these added materials. The aim of the present study was to determine the potential mineralization of separate and combined use of poultry manure (PM), wheat (Triticum aestivum L.) straw residues (WSR), and urea N (UN) applied to a loam soil and incubated periodically over 140 days period. Treatments included PM100, WSR100, PM50 + WSR50, UN100, UN50 + PM50, UN50 + WSR50, UN50 + PM25 + WSR25, and a control (unfertilized). Added amendments were applied on an N-equivalent basis at the rate of 200 mg N kg−1. Nitrogen supplying capacity of added materials was determined by measuring changes in total mineral N (ammonium-nitrogen and nitrate-nitrogen [NH4+–N + NO3––N]) and accumulation of NO3––N over different incubation periods. Changes in soil organic matter content and total N concentration were also monitored during the study. Results indicated that added amendments released substantial N into the mineral N pool (net cumulative N mineralized) [NCNM] ranged between 39 and 147 mg N kg−1, lowest in the WSR and highest in the UN50+PM50. Significant differences were observed among the amendments and the net inorganic N derived from a separate and combined use of PM was greater than the other treatments. Total inorganic N derived from PM increased from 2.3 mg kg−1 at d 1, to a maximum of 102 to 105 mg kg−1 at 63, 84 and 105 d after PM application. The values were further increase from 31.5 mg kg−1 at d 0 to a maximum of 165 mg kg−1 at d 49 in UN50 + PM50 treatment. The net cumulative N nitrified (NCNN) varied between 16 and 126 mg kg−1, highest in UN50 + PM50 treatment. Soil amended with WSR100 showed negative values both for mineralization and nitrification until day 84, displaying net immobilization. On average, percentage conversion of added N into available N by different amendments varied between 21% to 80%, while conversion of applied N into NO3––N ranged between 9% to 65%, and the treatment